PENGARUH KEPEMILIKAN SAHAM ASING, FINANCIAL DISTRESS, DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK DENGAN TEKANAN KEUANGAN SEBAGAI VARIABEL MODERASI - Abbas, Dirvi Surya; Dewi, Siti Ratna; Fauzia, Elsa; Wulida, Scherly Vigid; Utami, Gayatri (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study aims to determine the effect of foreign share ownership, financial distress, and sales growth variables on tax avoidance with financial pressure as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The research method used is quantitative with a purposive sampling approach, where 68 companies were sampled. The data used is secondary data taken from the company's financial statements and annual reports. The statistical tests used in this study are normality test analysis, multicollinearity, heteroscedasticity test, autocorrelation test, multiple linear regression test, coefficient of determination test, f test, and t test. The results of this study show that the results of the t and f tests show that: (1) foreign share ownership does not have a positive effect on tax avoidance (2) financial distress has a positive effect on tax avoidance (3) sales growth has a positive effect on tax avoidance (4) financial pressure moderates the effect of foreign share ownership on tax avoidance (5) financial pressure moderates the effect of financial distress on tax avoidance (6) financial pressure moderates the effect of sales growth on tax avoidance